A brief review on the validation of biology methods for COVID-19 detection - Chung, Le Thi Kim; Vung, Nguyen Dang; Uyen, Ngo Thi; Hanh, Bui Thi Minh; Huong, Le Thi; Hien, Pham Thi; Xuan, Le Thi Thanh; Ha, Nguyen Thuy; Dat, Dao Xuan (Frontiers in Tropical Diseases, 2022)
The COVID – 19 global pandemic has been going on for more than two years and the evolution of SARS-CoV-2 with many variants of concern still poses a risk to public health. Sufficient access to qualified and validated testing plays an important role in detecting, alerting the trend of the pandemic and provides evidences for making decision in preventive strategies, policies. Based on the method testing and laboratory condition, validation parameters (i.e., analytical sensitivity, limit of detection, diagnostic sensitivity, analytical specificity, diagnostic specificity, repeatability, reproducibility, robustness, positive predictive value, negative predictive value, applicability, practicability, time to results) are very different. With three main type of COVID-19 detection kits including nucleic acid, serological and antigen detection, what kind of validation parameters should be used becomes a complicated question and takes time to select. Our review provides a valuable and comprehensive information for other laboratories in assessment and selection the optimized parameters to validate new COVID-19 test kits.